Sharing transboundary resources : international law and optimal resource use - Benvenisti, Eyal (Cambridge studies in international and comparative law (Cambridge, England : 1996), 2002)
Why do states often use transboundary resources inefficiently? Benvenisti considers a range of factors, including mismanagement as a link between domestic and international processes. He also looks forward to potential solutions in this multi-disciplinary approach. Benvenisti's analysis will interest international environmentalists and lawyers, and international relations scholars and practitioners.